2021
DOI: 10.3348/kjr.2020.0310
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Assessment of Monoenergetic and Polyenergetic Images Acquired by Dual-Energy CT in Breast Cancer

Abstract: Objective To objectively and subjectively assess and compare the characteristics of monoenergetic images [MEI (+)] and polyenergetic images (PEI) acquired by dual-energy CT (DECT) of patients with breast cancer. Materials and Methods This retrospective study evaluated the images and data of 42 patients with breast cancer who had undergone dual-phase contrast-enhanced DECT from June to September 2019. One standard PEI, five MEI (+) in 10-kiloelectron volt (keV) intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Regarding the visualization effect of the dual-energy dataset on the early vascular invasion of MESSMT, we found that lesion visualization with 40 keV reconstruction images is better than other VMIs, while color-coded ID and Zeff reconstructed images also achieve satisfactory performance. This finding is similar to previous research results ( 8 , 9 , 25 ). Based on objective assessment of the image quality, higher CNR corresponds to lower keV because higher CT attenuation of the vein lesions leads to higher contrast to the background.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding the visualization effect of the dual-energy dataset on the early vascular invasion of MESSMT, we found that lesion visualization with 40 keV reconstruction images is better than other VMIs, while color-coded ID and Zeff reconstructed images also achieve satisfactory performance. This finding is similar to previous research results ( 8 , 9 , 25 ). Based on objective assessment of the image quality, higher CNR corresponds to lower keV because higher CT attenuation of the vein lesions leads to higher contrast to the background.…”
Section: Discussionsupporting
confidence: 93%
“…Virtual monoenergetic images derived from DECT have been shown to improve soft tissue contrast and increase the conspicuity of solid organ lesions ( 24 ). Color-coded iodine density and Z effective reconstruction images have also been proven to perform well in the subjective assessment of lesions since the human eye is more sensitive to color than to grayscale ( 25 ). Regarding the visualization effect of the dual-energy dataset on the early vascular invasion of MESSMT, we found that lesion visualization with 40 keV reconstruction images is better than other VMIs, while color-coded ID and Zeff reconstructed images also achieve satisfactory performance.…”
Section: Discussionmentioning
confidence: 99%
“…Dual-energy CT can obtain multiparameter images such as substance separation, virtual single energy, effective atomic number, and energy spectrum curve, which can qualitatively and quantitatively provide more valuable information for the differential diagnosis of lesions, determination of pathological types and aggressiveness of cancers, and prediction of efficacy of neoadjuvant therapy [ 18 , 23 25 ]. However, the multiparameters of DECT are rarely used for esophageal cancer staging.…”
Section: Discussionmentioning
confidence: 99%
“…For each thigh, visualization of the branch order of the descending branches of the lateral circumflex femoral artery was assessed with a 5-point scale: 5, excellent (fourth-order or higher-order branches); 4, superior (third-order branches); 3, diagnostic (second-order branches); 2, suboptimal (main- or first-order branches); and 1, poor (vessels not seen) 14 . For each thigh, the image quality was scored as follows: 5, sharp anatomical structure and satisfactory details; 4, less clear anatomical structure and details; 3, decreased confidence in details but the anatomical structure is still relatively clear; 2, poor details and anatomical structure difficult to make out; and 1, unacceptable anatomical structure and details 15 . For each cutaneous perforator, the vascular network continuity of the perforator was assessed on a 3-point scale: 2, well continuous, the course of the perforators and their source arteries could be identified easily; 1, discontinuous, but the course of the perforators and their source arteries could be identified through the upper and lower slices; 0, discontinuous, and the course of perforators and their source arteries could not be identified.…”
Section: Methodsmentioning
confidence: 99%